Four classical methods in solving inequalities - Rashidi, Farzad (Eximia, 2022)
In this article, we want to examine 3 classic methods in proving inequalities. The first method is Jensen’s inequality, which can be proved by defining a function. The second method is known as the pqr method, in which inequality is expressed in terms of a polynomial.In the next section, we will look at the idea of S.O.S. The next method is Chinese Dumbass, in which the inequality can be proved using a triangle.